1997
DOI: 10.1007/bf02303791
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node uptake of two different technetium-labeled radiocolloids

Abstract: [99mTc]SC is rapidly and efficiently taken up by lymphatics at the primary injection site, is significantly retained in the SLN, and flows slowly to the next echelon node (FLN or ILN) and to the systemic circulation (SP). [99mTc]HSA tends to accumulate less efficiently in the SLN and to disperse more rapidly to the next echelon nodes and to the systemic circulation. By extrapolation, [99mTc]SC is likely to be a better radiocolloid for the intraoperative detection of SLNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…29 Similarly, decreased radioactivity counts of SLNs, a decreased ratio of SLN and non-SLN counts, and a faster decrease of the SLN count over time were noted when 99m Tc-HSA was used than when unfiltered 99m Tc-sulfur colloid was used. 30 These results, and ours, suggest that 99m Tc-HSA is less effective than other radioactive colloids.…”
Section: Discussionmentioning
confidence: 93%
“…29 Similarly, decreased radioactivity counts of SLNs, a decreased ratio of SLN and non-SLN counts, and a faster decrease of the SLN count over time were noted when 99m Tc-HSA was used than when unfiltered 99m Tc-sulfur colloid was used. 30 These results, and ours, suggest that 99m Tc-HSA is less effective than other radioactive colloids.…”
Section: Discussionmentioning
confidence: 93%
“…The rapidity with which the second pattern replaces the first may depend on the size of tracer particle used. Larger particles have slower kinetics, 10,12,22 which may lead to a longer persistence of distribution determined by lymph flow. Our previous clinical study found significantly more radioactive nodes and lower concordance with blue dye when SC was used.…”
Section: Discussionmentioning
confidence: 98%
“…8 Larger particles were believed to be too large to efficiently enter lymphatic vessels, and smaller particles were absorbed by blood capillaries. Comparisons of the commercially available tracers, human serum albumin (HSA; ϳ10 nm), sulfur colloid (SC; 50 -300ϩ nm), and albumin colloid (200 -1000 nm), 9 in patients and animal models revealed more rapid transit of HSA to higher echelon nodes, 10 similar levels of specific activity in draining nodes, 9 equal efficacy in SLN identification, 11 and a consistent requirement for early imaging in lymphoscintigraphy to capture the first draining node. 12 We have previously confirmed the effectiveness of both HSA and SC, but found that significantly more nodes were removed in patients injected with SC than with HSA.…”
mentioning
confidence: 91%
“…In addition, in contrast to the blue dye, the colloid has a much longer retention time and may be concentrated in the SLN. Studies from MCC [4] and Henry Ford Hospital [5] have shown that the localization ratios double if the harvest occurs 2-4 hours after the injection of the radiocolloid compared to performing the mapping immediately after the injection of the radiocolloid.…”
Section: Description Of the Technique Of Intraoperative Lymphatic Mapmentioning
confidence: 97%